Generalized g-fractional calculus and iterative methods - ANASTASSIOU, George A.; ARGYROS, Ioannis K. (Studia Universitatis Babeș-Bolyai Mathematica, 2016)
We approximated solutions of some iterative methods on a generalized Banach space setting in [5]. Earlier studies such as [7-12] the operator involved is Frechet-differentiable. In [5] we assumed that the operator is only continuous. This way we extended the applicability of these methods to include generalized fractional calculus and problems from other areas. In the present study applications include generalized g-fractional calculus. Fractional calculus is very important for its applications in many applied sciences. Mathematics Subject Classiffcation (2010): 26A33, 65G99, 47J25.